The Limits of Organic Life in Planetary Systems - National Research Council (The National Academies Press, 2007)
The search for life in the solar system and beyond has to date been governed by a model based on what we know about life on Earth (terran life). Most of NASA's mission planning is focused on locations where liquid water is possible and emphasizes searches for structures that resemble cells in terran organisms. It is possible, however, that life exists that is based on chemical reactions that do not involve carbon compounds, that occurs in solvents other than water, or that involves oxidation-reduction reactions without oxygen gas. To assist NASA incorporate this possibility in its efforts to search for life, the NRC was asked to carry out a study to evaluate whether nonstandard biochemistry might support life in solar system and conceivable extrasolar environments, and to define areas to guide research in this area. This book presents an exploration of a limited set of hypothetical chemistries of life, a review of current knowledge concerning key questions or hypotheses about nonterran life, and suggestions for future research.
Keywords: Space and Aeronautics

Practical Applications of a Space Station - National Research Council (The National Academies Press, 1984)
The demonstrated capabilities of the Space Shuttle and rapid advancements in both ground- and space-based technology offer new opportunities for developing space systems for practical use, including a manned space station and one or more unmanned space platforms. The Space Applications Board conducted a study to determine the technical requirements that should be considered in the conceptual design of a space station and/or space platforms so that, if developed, these spacecraft would have utility for practical applications. Practical Applications of a Space Station is a formal report of the study, in which six panels met, one in each of the following areas: earth's resources, earth's environment, ocean operations, satellite communications, materials science and engineering, and system design factors. Each panel was asked to consider what practical applications of space systems may be expected in their particular areas beginning around 1990. The panels were also asked to identify technological progress that would need to be made and that should be emphasized in order for space systems with practical uses to have greater utility by the time a space station might be available.
Keywords: Earth Sciences

Vision and Voyages for Planetary Science in the Decade 2013-2022 - National Research Council (The National Academies Press, 2011)
In recent years, planetary science has seen a tremendous growth in new knowledge. Deposits of water ice exist at the Moon's poles. Discoveries on the surface of Mars point to an early warm wet climate, and perhaps conditions under which life could have emerged. Liquid methane rain falls on Saturn's moon Titan, creating rivers, lakes, and geologic landscapes with uncanny resemblances to Earth's. Vision and Voyages for Planetary Science in the Decade 2013-2022 surveys the current state of knowledge of the solar system and recommends a suite of planetary science flagship missions for the decade 2013-2022 that could provide a steady stream of important new discoveries about the solar system. Research priorities defined in the report were selected through a rigorous review that included input from five expert panels. NASA's highest priority large mission should be the Mars Astrobiology Explorer Cacher (MAX-C), a mission to Mars that could help determine whether the planet ever supported life and could also help answer questions about its geologic and climatic history. Other projects should include a mission to Jupiter's icy moon Europa and its subsurface ocean, and the Uranus Orbiter and Probe mission to investigate that planet's interior structure, atmosphere, and composition. For medium-size missions, Vision and Voyages for Planetary Science in the Decade 2013-2022 recommends that NASA select two new missions to be included in its New Frontiers program, which explores the solar system with frequent, mid-size spacecraft missions. If NASA cannot stay within budget for any of these proposed flagship projects, it should focus on smaller, less expensive missions first. Vision and Voyages for Planetary Science in the Decade 2013-2022 suggests that the National Science Foundation expand its funding for existing laboratories and establish new facilities as needed. It also recommends that the program enlist the participation of international partners. This report is a vital resource for government agencies supporting space science, the planetary science community, and the public.
Keywords: Space and Aeronautics

The Astrophysical Context of Life - National Research Council (The National Academies Press, 2005)
In 1997, the National Aeronautics and Space Administration (NASA) formed the National Astrobiology Institute to coordinate and fund research into the origins, distribution, and fate of life in the universe. A 2002 NRC study of that program, Life in the Universe: An Assessment of U.S. and International Programs in Astrobiology, raised a number of concerns about the Astrobiology program. In particular, it concluded that areas of astrophysics related to the astronomical environment in which life arose on earth were not well represented in the program. In response to that finding, the Space Studies Board requested the original study committee, the Committee on the Origins and Evolution of Life, to examine ways to augment and integrate astronomy and astrophysics into the Astrobiology program. This report presents the results of that study. It provides a review of the earlier report and related efforts, a detailed examination of the elements of the astrobiology program that would benefit from greater integration and augmentation of astronomy and astrophysics, and an assessment of ways to facilitate the integration of astronomy with other astrobiology disciplines.
Keywords: Space and Aeronautics

Report of the Committee on a Commercially Developed Space Facility - National Research Council (The National Academies Press, 1989)
The Committee on a Commercially Developed Space Facility assessed the scientific and commercial benefit to the nation of having a CDSF in place prior to Space Station operations. The committee examined planned and anticipated microgravity research and manufacturing requirements of the federal government and commercial users as well as the extent to which existing, planned, and proposed capabilities and infrastructure could support these requirements. The committee's findings concentrate on the desirability of having an additional space facility in service to the interim preceding Space Station Freedom.
Keywords: Space and Aeronautics

Earth Science and Applications from Space: A Midterm Assessment of NASA's Implementation of the Decadal Survey - National Research Council (The National Academies Press, 2012)
Understanding the effects of natural and human-induced changes on the global environment and their implications requires a foundation of integrated observations of land, sea, air and space, on which to build credible information products, forecast models, and other tools for making informed decisions. The 2007 National Research Council report on decadal survey called for a renewal of the national commitment to a program of Earth observations in which attention to securing practical benefits for humankind plays an equal role with the quest to acquire new knowledge about the Earth system. NASA responded favorably and aggressively to this survey, embracing its overall recommendations for Earth observations, missions, technology investments, and priorities for the underlying science. As a result, the science and applications communities have made significant progress over the past 5 years. However, the Committee on Assessment of NASA's Earth Science Program found that the survey vision is being realized at a far slower pace than was recommended, principally because the required budget was not achieved. Exacerbating the budget shortfalls, NASA Earth science programs experienced launch failures and delays and the cost of implementing missions increased substantially as a result of changes in mission scope, increases in launch vehicle costs and/or the lack of availability of a medium-class launch vehicle, under-estimation of costs by the decadal survey, and unfunded programmatic changes that were required by Congress and the Office of Management and Budget. In addition, the National Oceanic and Atmospheric Administration (NOAA) has made significant reductions in scope to its future Earth environmental observing satellites as it contends with budget shortfalls. Earth Science and Applications from Space: A Midterm Assessment of NASA's Implementation of the Decadal Survey recommends a number of steps to better manage existing programs and to implement future programs that will be recommended by the next decadal survey. The report also highlights the urgent need for the Executive Branch to develop and implement an overarching multiagency national strategy for Earth observations from space, a key recommendation of the 2007 decadal survey that remains unfulfilled.
Keywords: Space and Aeronautics; Earth Sciences

One Universe: At Home in the Cosmos - Neil de Grasse Tyson; Charles Liu; Robert Irion (The National Academies Press, 2000)
A new window opens onto the cosmos... Almost every day we are challenged by new information from the outermost reaches of space. Using straightforward language, One Universe explores the physical principles that govern the workings of our own world so that we can appreciate how they operate in the cosmos around us. Bands of color in a sunlit crystal and the spectrum of starlight in giant telescopes, the arc of a hard-hit baseball and the orbit of the moon, traffic patterns on a freeway and the spiral arms in a galaxy full of stars—they're all tied together in grand and simple ways. We can understand the vast cosmos in which we live by exploring three basic concepts: motion, matter, and energy. With these as a starting point, One Universe shows how the physical principles that operate in our kitchens and backyards are actually down-to-Earth versions of cosmic processes. The book then takes us to the limits of our knowledge, asking the ultimate questions about the origins and existence of life as we know it and where the universe came from—and where it is going. Glorious photographs—many seen for the first time in these pages—and original illustrations expand and enrich our understanding. Evocative and clearly written, One Universe explains complex ideas in ways that every reader can grasp and enjoy. This book captures the grandeur of the heavens while making us feel at home in the cosmos. Above all, it helps us realize that galaxies, stars, planets, and we ourselves all belong to One Universe.
Keywords: Explore Science; Space and Aeronautics

Scientific Uses of the Space Shuttle (The National Academies Press, 1974)
Scientific Uses of the Space Shuttle focuses on those aspects of the Shuttle most different from conventional launch-vehicle capabilities. It especially considers the sortie mode, in which the Shuttle carries into orbit a payload that remains attached to the Shuttle and then returns to earth with the payload after one to four weeks. Interest in the sortie mode is particularly great because of the contemporary decision by several European countries to develop a space laboratory (Spacelab). The report also considers the use of the Shuttle for launching, servicing, and recovering satellites and for launching lunar, planetary, and interplanetary missions.
Keywords: Space and Aeronautics

Defending Planet Earth: Near-Earth-Object Surveys and Hazard Mitigation Strategies - National Research Council (The National Academies Press, 2010)
The United States spends approximately $4 million each year searching for near-Earth objects (NEOs). The objective is to detect those that may collide with Earth. The majority of this funding supports the operation of several observatories that scan the sky searching for NEOs. This, however, is insufficient in detecting the majority of NEOs that may present a tangible threat to humanity. A significantly smaller amount of funding supports ways to protect the Earth from such a potential collision or "mitigation." In 2005, a Congressional mandate called for NASA to detect 90 percent of NEOs with diameters of 140 meters of greater by 2020. Defending Planet Earth: Near-Earth Object Surveys and Hazard Mitigation Strategies identifies the need for detection of objects as small as 30 to 50 meters as these can be highly destructive. The book explores four main types of mitigation including civil defense, "slow push" or "pull" methods, kinetic impactors and nuclear explosions. It also asserts that responding effectively to hazards posed by NEOs requires national and international cooperation. Defending Planet Earth: Near-Earth Object Surveys and Hazard Mitigation Strategies is a useful guide for scientists, astronomers, policy makers and engineers.
Keywords: Space and Aeronautics

Severe Space Weather Events: Understanding Societal and Economic Impacts: A Workshop Report - National Research Council (The National Academies Press, 2008)
The adverse effects of extreme space weather on modern technology—power grid outages, high-frequency communication blackouts, spacecraft anomalies—are well known and well documented, and the physical processes underlying space weather are also generally well understood. Less well documented and understood, however, are the potential economic and societal impacts of the disruption of critical technological systems by severe space weather. As a first step toward determining the socioeconomic impacts of extreme space weather events and addressing the questions of space weather risk assessment and management, a public workshop was held in May 2008. The workshop brought together representatives of industry, the government, and academia to consider both direct and collateral effects of severe space weather events, the current state of the space weather services infrastructure in the United States, the needs of users of space weather data and services, and the ramifications of future technological developments for contemporary society's vulnerability to space weather. The workshop concluded with a discussion of un- or underexplored topics that would yield the greatest benefits in space weather risk management.
Keywords: Space and Aeronautics

NASA Space Technology Roadmaps and Priorities: Restoring NASA's Technological Edge and Paving the Way for a New Era in Space - National Research Council (The National Academies Press, 2012)
NASA's Office of the Chief Technologist (OCT) has begun to rebuild the advanced space technology program in the agency with plans laid out in 14 draft technology roadmaps. It has been years since NASA has had a vigorous, broad-based program in advanced space technology development and its technology base has been largely depleted. However, success in executing future NASA space missions will depend on advanced technology developments that should already be underway. Reaching out to involve the external technical community, the National Research Council (NRC) considered the 14 draft technology roadmaps prepared by OCT and ranked the top technical challenges and highest priority technologies that NASA should emphasize in the next 5 years. This report provides specific guidance and recommendations on how the effectiveness of the technology development program managed by OCT can be enhanced in the face of scarce resources.
Keywords: Space and Aeronautics

Recapturing a Future for Space Exploration: Life and Physical Sciences Research for a New Era - National Research Council (The National Academies Press, 2011)
More than four decades have passed since a human first set foot on the Moon. Great strides have been made in our understanding of what is required to support an enduring human presence in space, as evidenced by progressively more advanced orbiting human outposts, culminating in the current International Space Station (ISS). However, of the more than 500 humans who have so far ventured into space, most have gone only as far as near-Earth orbit, and none have traveled beyond the orbit of the Moon. Achieving humans' further progress into the solar system had proved far more difficult than imagined in the heady days of the Apollo missions, but the potential rewards remain substantial. During its more than 50-year history, NASA's success in human space exploration has depended on the agency's ability to effectively address a wide range of biomedical, engineering, physical science, and related obstacles—an achievement made possible by NASA's strong and productive commitments to life and physical sciences research for human space exploration, and by its use of human space exploration infrastructures for scientific discovery. The Committee for the Decadal Survey of Biological and Physical Sciences acknowledges the many achievements of NASA, which are all the more remarkable given budgetary challenges and changing directions within the agency. In the past decade, however, a consequence of those challenges has been a life and physical sciences research program that was dramatically reduced in both scale and scope, with the result that the agency is poorly positioned to take full advantage of the scientific opportunities offered by the now fully equipped and staffed ISS laboratory, or to effectively pursue the scientific research needed to support the development of advanced human exploration capabilities. Although its review has left it deeply concerned about the current state of NASA's life and physical sciences research, the Committee for the Decadal Survey on Biological and Physical Sciences in Space is nevertheless convinced that a focused science and engineering program can achieve successes that will bring the space community, the U.S. public, and policymakers to an understanding that we are ready for the next significant phase of human space exploration. The goal of this report is to lay out steps and develop a forward-looking portfolio of research that will provide the basis for recapturing the excitement and value of human spaceflight—thereby enabling the U.S. space program to deliver on new exploration initiatives that serve the nation, excite the public, and place the United States again at the forefront of space exploration for the global good.
Keywords: Space and Aeronautics